PENERAPAN PENDEKATAN CRT MELALUI PERMAINAN TRADISIONAL ENGKLEK UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS PESERTA DIDIK KELAS V - Natalia, Krismi; Vivi Rulviana; Aning Triastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to improve the English learning outcomes of fifth-grade students of SDN Uteran 01 Madiun through the implementation of the Culturally Responsive Teaching (CRT) approach using the traditional game engklek. The research employs a classroom action research method conducted in two cycles, with each cycle consisting of the stages of planning, acting, observing, and reflecting. The results show that the application of CRT through the engklek game successfully enhanced students’ learning outcomes, as evidenced by an increase in the average student scores that exceeded the Learning Achievement Criteria (KKTP). Furthermore, student motivation and engagement in the learning process also significantly improved. Thus, this approach can be an effective alternative for more contextual and meaningful English learning.